2015
DOI: 10.4137/ccrpm.s23327
|View full text |Cite
|
Sign up to set email alerts
|

Organizing Pneumonia in Rheumatoid Arthritis Patients: A Case-Based Review

Abstract: We treated 21 patients with organizing pneumonia (OP) associated with rheumatoid arthritis (RA) or related to biological disease-modifying antirheumatic drugs (DMARDs) at our institution between 2006 and 2014. Among these cases, 3 (14.3%) preceded articular symptoms of RA, 4 (19.0%) developed simultaneously with RA onset, and 14 (66.7%) occurred during follow-up periods for RA. In the case of OP preceding RA, increased levels of anti-cyclic citrullinated peptide antibodies and rheumatoid factor were observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 97 publications
2
22
0
Order By: Relevance
“…This proportion of cases in our study is similar to those reported in previous studies: 11% [14] or 14% [22] of RA-OP patients. Meanwhile, the di culty in differentiating RA-OP from bacterial pneumonia in clinical practice may be, in part, explained by our ndings: 42% of the OP events showed unilateral shadows, 76% had normal KL-6 titres, and most patients presented with u-like symptoms, all of which are the typical characteristics of bacterial pneumonia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This proportion of cases in our study is similar to those reported in previous studies: 11% [14] or 14% [22] of RA-OP patients. Meanwhile, the di culty in differentiating RA-OP from bacterial pneumonia in clinical practice may be, in part, explained by our ndings: 42% of the OP events showed unilateral shadows, 76% had normal KL-6 titres, and most patients presented with u-like symptoms, all of which are the typical characteristics of bacterial pneumonia.…”
Section: Discussionsupporting
confidence: 92%
“…Our study clari ed that 30% of the patients with RA-OP experienced OP recurrence even with proper glucocorticoid treatment. This proportion corresponds to those in previous reports on RA-OP: 21% [14] or 10% [22]. These proportions of RA-OP might be lower than in those of cryptogenic OP: 58% [28], 56% [29], 30% [26], or 27% [27].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…According to a case-based review, the PSL dosage for OP in patients with RA was 25-60 mg/day or 1-1.5 mg/kg/day (17). In Case 1, although CAM was ceased due to its adverse side effect of diarrhea, when OP shadows grew worse with PSL (5 mg/day) treatment, CAM was successfully added to the treatment.…”
Section: Discussionmentioning
confidence: 99%